Dual-use research of concern landscape in Southeast Asia: prioritisation, gaps, and challenges - Caballero-Anthony, Mely (2025)
This article examines the governance of Dual Use Research of Concern (DURC) in Southeast Asia, highlighting both progress and persistent gaps in biosafety and biosecurity. While significant developments have been made in biosafety and biosecurity, the region remains underprepared to address the complexities of DURC. This under-preparedness stems from diverse factors, including varying levels of exposure to biosecurity threats across countries, competing priorities within national biosecurity agendas, limited awareness of DURC issues, and weak institutional capacity to implement effective oversight mechanisms. These factors create inconsistencies in the implementation of DURC governance across countries, undermining efforts to establish robust safeguards against potential misuse of scientific research. The article argues that addressing these domestic issues is crucial for building more effective DURC governance frameworks. Strengthening national policies, improving institutional capabilities, and fostering awareness of DURC risks are essential steps toward mitigating biosecurity threats and ensuring the responsible conduct of research within the region.